2018
DOI: 10.1038/s41598-018-35452-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune Signatures of Novel Adjuvant Formulations Using Machine Learning

Abstract: Adjuvants have long been critical components of vaccines, but the exact mechanisms of their action and precisely how they alter or enhance vaccine-induced immune responses are often unclear. In this study, we used broad immunoprofiling of antibody, cellular, and cytokine responses, combined with data integration and machine learning to gain insight into the impact of different adjuvant formulations on vaccine-induced immune responses. A Self-Assembling Protein Nanoparticles (SAPN) presenting the malarial circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…MD simulation has been applied in epitopecarrier fusion construction in HIV vaccine and malaria vaccine (19,20). The machine learning tool was used to predict the antigen-specific immune signatures in vaccines based on immune profiling data (21,22). Ong et al (2020) predicted possible vaccine targets of COVID-19 using a machine learning tool, including the non-structural protein (nsp3), a novel target that has not been tested for vaccines (23).…”
Section: Information Technology Accelerate Covid-19 Vaccine Developmementioning
confidence: 99%
“…MD simulation has been applied in epitopecarrier fusion construction in HIV vaccine and malaria vaccine (19,20). The machine learning tool was used to predict the antigen-specific immune signatures in vaccines based on immune profiling data (21,22). Ong et al (2020) predicted possible vaccine targets of COVID-19 using a machine learning tool, including the non-structural protein (nsp3), a novel target that has not been tested for vaccines (23).…”
Section: Information Technology Accelerate Covid-19 Vaccine Developmementioning
confidence: 99%
“…Indeed, Chaudhury et al showed that the sole use of such analysis is too reductive to identify differences between immune responses. Indeed, their predictive model of the malaria vaccine-induced immune response also integrates other immune parameters, such as IL-4 and IL-6 levels, which are variables of importance in different tissues such as blood or liver [32]. Years of immune system screening have demonstrated that immune responses to pathogens and vaccines are highly multifactorial and involve numerous diverse actors.…”
Section: What Types Of Biomarkers Can Be Used To Define Vaccine Signatures?mentioning
confidence: 99%
“…This information can be used to identify new correlates of protection from infection and lead to a more comprehensive understanding of vaccine mechanisms that underlie protection (35,36). Systems serology has been applied to search for immune features that best predict protection induced by HIV vaccines (37)(38)(39), malaria vaccines (40)(41)(42), and other vaccines (43,44). In the present study, we developed a systems serology pipeline that integrated both machine learning and Cox proportional hazards regression to analyze high-dimensional Fc array data.…”
Section: Discussionmentioning
confidence: 99%